An Engineering-to-Biology Thesaurus To Promote Better Collaboration, Creativity and Discovery - Stroble, J. K.; Stone, R. B.; McAdams, D. A.; Watkins, S. E. (Cranfield University Press, 2009)
Biological inspiration for engineering design has occurred through a variety of techniques such as database searches, keyword and antonym searches, knowledge of biology, observations of nature and other “aha” moments. This research aims to alleviate the knowledge gap problem by providing a link between engineering and biology with a thesaurus. The biologically connotative terms that comprise the thesaurus were collected utilizing an organized verb-noun search; collocated words were extracted from texts based on a functional search word. This thesaurus should enable the engineering and biology communities to better collaborate, create and discover.
Organised by: Cranfield University
Keywords: Engineering design; Function; Analogical reasoning